DETENTION IN THE DISCIPLINARY BATTALION: COMPARATIVE LEGAL ANALYSIS OF PUNISHMENT IN UKRAINE AND IN GREAT BRITAIN - Nesterenko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
This article is devoted to a comparative legal analysis of the procedure and conditions of execution and serving of punishment in the form of detention in a disciplinary battalion in Ukraine and punishment in the form of detention in a military corrective training center in Great Britain. Legal regulation of the responsibility of servicemen for committing offenses is reflected in the laws on the Armed Forces and articles of normative legal documents, such as criminal codes of different countries of the world. The current state of the reform of the Armed Forces of Ukraine against the background of the Russia’s military aggression on the sovereign territory of Ukraine leads to a more thorough analysis of the existing system of servicemen’ punishment for offenses committed by them, and any issue related to bringing the national Armed Forces to NATO standards is of high public interest and has a privileged significance. The conducted comparative legal analysis of the procedure and conditions of execution and serving of punishment in the form of detention in a disciplinary battalion in Ukraine and a similar unit of the Armed Forces of a NATO member country will provide scholars and other interested parties with an objective analysis of the effectiveness of this type of punishment, ensure the quality of execution of this type of punishment and inform national legislators about the existing models of functioning of this type of punishment. According to the results of this study, we proposed directions for the development of the disciplinary battalion of Ukraine, as well as measures for correction and resocialization of convicted servicemen, which will meet the needs of the servicemen themselves and ensure the protection of their rights and interests, as well as contribute to the formation of mechanisms of legal socialization and law-abiding behavior in their personality. Thus, the positive practices of correction and re-socialization of servicemen, quantitative indicators of recidivism, peculiarities of the material and technical base of the military corrective training center in Great Britain, proposed amendments to the legislation, as well as options for additional independent subjects of monitoring and control over the order and conditions of serving the sentence in the form of detention in a disciplinary battalion were highlighted.